Genetic analysis for gestation length, birth weight, weaning weight, and accumulated productivity in Nellore beef cattle - Chud, Tatiane C. S. [UNESP]; Caetano, Sabrina L.; Buzanskas, Marcos E. [UNESP]; Grossi, Daniela A.; Guidolin, Diego G. F.; Nascimento, Guilherme B. [UNESP]; Rosa, Jaqueline O. [UNESP]; Lobo, Raysildo B.; Munari, Danisio P. [UNESP] (Elsevier B.V., 2014)
The aim of this study was to estimate variance and covariance components for gestation length (GL), birth weight (BW), weaning weight (WW), and accumulated productivity (ACP), and their respective genetic trends for Nellore cattle raised in Brazil. The ACP trait is a reproduction index developed by the National Association of Breeders and Researchers (ANCP) and comprises the total number of calves born per dam, weight of weaned calves, and age of the dam at calving. A total of 25,085, 46,911, 50,044, and 7351 observations were considered to analyze GL, BW, WW, and ACP. Genetic parameters were estimated by the Average Information Restricted Maximum Likelihood method in single and two-trait analyses. The average direct heritability estimates obtained in two-trait analyses were equal to 0.38 +/- 0.03 (GL), 0.25 +/- 0.02 (BW), 0.28 +/- 0.02 (WW), and 0.11 +/- 0.02 (ACP). The highest genetic correlation was found between BW and WW (0.36 +/- 0.05), followed by BW and ACP (0.20 +/- 0.09), and BW and GL (0.19 +/- 0.06). Significant direct genetic trends (P < 0.001) were observed for GL, BW, and WW equal to -0.027 days per year, 0.073 kg per year, and 0.8456 kg per year, respectively. Greater emphasis should be given to accumulated productivity and gestation length traits in order to increase the number and weight of weaned calves. As accumulated productivity presents low heritability estimates, genetic improvement through selection could be slow in the Nellore breed. Our study reports genetic progress for weaning weight, since its genetic trend has increased over the years. Similar genetic trend for birth weight was observed, which may be a consequence of selection towards higher body weights at older ages. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Breeding values; Genetic trend; Growth and reproductive traits; Zebu cattle